Analisis Implementasi Kebijakan Sistem Kerja pada Pemerintah Daerah Kabupaten Paser - Decy Mutia Suhartini; Agus Priyanto; Rina Yulianti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In the context of bureaucratic simplification, the President of the Republic of Indonesia has mandated the implementation of bureaucratic reform, which consists of three stages of transformation: organizational transformation, position transformation, and performance management transformation. With this bureaucratic transformation, civil servants (ASN) are required to be able to adapt and perform in order to achieve organizational performance through a more agile working system. In the Paser Regency Government, bureaucratic transformation has been carried out up to the stage of policy implementation efforts on the working system through Paser Regent Regulation Number 9 of 2024. Meanwhile, within the East Kalimantan Provincial Government, as of June 2024, almost 90.9% of Provincial/City and Regency Governments have prepared working system guidelines, with only around 45.5% or five city/regency governments still in the facilitation and drafting stages. This shows that efforts to implement policies at the regional level have begun. However, the implementation of the working system itself, even after the Working System Guidelines were established, has not yet been followed up as expected in the phase of work system adjustments—namely changes in work mechanisms and business processes. Regarding the transformation of the working system into stages of policy implementation—including socialization activities, drafting of technical policy guidelines, resource allocation, capacity building and training, and full implementation (including monitoring, evaluation, and performance appraisal)—these must be carried out immediately. This is so that the policy can serve as a reference to fully assess the impact of bureaucratic reform after going through the three stages of transformation. This research was conducted to assess the extent of the policy implementation efforts of the Regulation of the Minister for Administrative and Bureaucratic Reform (Permenpan RB) Number 7 of 2022 concerning the Working System in the regions, and what obstacles are faced by local governments, especially in Paser Regency, in the steps of its implementation. The research results show that changes in performance management positively affect ASN performance and have an impact on public service performance. Implementation of the working system in accordance with Permenpan RB Number 7 of 2022 must be followed up with more dynamic changes so that performance targets, performance agreements, and the working system can be integrated and continuous.